2013
DOI: 10.1111/cfs.12093
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration: self‐reported successful collaboration by teachers and social workers in multidisciplinary teams

Abstract: A B S T R AC TThe aim of this paper is to address facilitators for successful interprofessional collaboration (IPC) between social workers (SWs) and teachers. Individual interviews were carried out with seven SWs employed in municipal child welfare services and six teachers from primary and secondary schools. The informants had at least two years' experience within multidisciplinary teams. The transcripts were analysed using an inductive thematic approach and the NVIVO9 computer software package for qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
0
42
0
4
Order By: Relevance
“…The leadership and the motivation dimensions imply whether interprofessional groups have a successful management and give participants opportunities to develop and do something valuable through participation in interprofessional collaboration. These dimensions have been mentioned by previous research as important in achieving a successful interprofessional collaboration (Cameron et al, 2014;Hesjedal et al, 2015). Again, teachers have been in a limited degree included in the work with the LOG model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leadership and the motivation dimensions imply whether interprofessional groups have a successful management and give participants opportunities to develop and do something valuable through participation in interprofessional collaboration. These dimensions have been mentioned by previous research as important in achieving a successful interprofessional collaboration (Cameron et al, 2014;Hesjedal et al, 2015). Again, teachers have been in a limited degree included in the work with the LOG model.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study by Altshuler (2003) among students, educators, and caseworkers pinpoints definition of roles, guidelines regarding confidential information, and supportive networks at schools as important to obtaining successful collaboration. Accordingly, the study conducted by Hesjedal, Hetland, and Iversen (2015) revealed that personal commitment, equality, and common goals also facilitate interprofessional collaboration.…”
Section: Barriers and Facilitators Of Interprofessional Collaborationmentioning
confidence: 99%
“…The results indicated that there were significant improvements in attitudes, equality in care provision and team work (Curran, Mugford, Law, & MacDonald, 2005;Willumsen & Hallberg, 2003). In addition, Andrew et al (2008) in their study on community of practice in nursing concluded that the quality and the complexity of the work done can be promoted through collaboration with service providers, university based academics and researchers (Hesjedal, Hetland, & Iversen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is spirituality, loving relationships with family or connection and laughter with colleagues, they are protective factors for working with trauma (Holloway and Moss, 2010;Friedman-Krauss et al, 2014;Hall and Souers, 2015;Hesjedal et al, 2015). It is fundamental when working with traumatized children that a professional remains calm and be at peace with themselves and the world around them, so they can respond effectively to a child in a state of hyper-arousal (Bloom, 1995;Downey, 2007;Brunzell et al, 2015b).…”
Section: Diagram-1 Teaching Traumatised Childrenmentioning
confidence: 99%